Sound Absorption Performance of Ink-Tube Waste as Absorber - Abdul Rahim, Marham; Samsudin, Emedya Murniwaty (Recent Trends in Civil Engineering and Built Environment, 2021)
Plastic waste generation is increasing with the rapid development and increasing human population. Improper plastic waste management contributes to many devastating effects on humans and to the environment. The utilization of recycling plastic waste to local industry was implemented in ensuring less accumulated waste production. This study aimed to utilizing empty ink-tube plastic from unused pen as the core material for sound absorber. The effectiveness of the material to be used for the sound absorption panel is tested in different lengths of the ink-tube with various placement of the cotton layer on the samples. Measurement of sound absorption coefficient is done using impedance tube ranging from 350 Hz to 5000 Hz frequencies. The result shows that tubes with 3 cm and 5 cm length able to absorb more sound with the presence of cotton layered at the front and backside of the sample. The absorption coefficients reached 0.79 at 2000 Hz and 0.95 at 1250 Hz for 3 cm and 5 cm samples, respectively. Findings also show that introducing a cotton layer covering the front side of the sample able to enhance the absorption coefficients of the ink-tube absorber at a wider frequency sector.